Effects of dietary roughage neutral detergent fiber levels and flint corn processing method on growth performance, carcass characteristics, feeding behavior, and rumen morphometrics of Bos indicus cattle. (10th June 2019) - de Melo, Antonio Humberto F; Marques, Rodrigo S; Gouvêa, Vinícius N; de Souza, Jonas; Batalha, Camila D A; Basto, Débora C; Millen, Danilo D; Drouillard, James S; Santos, Flávio A P
Abstract: Flint corn processing method [coarse ground corn (CGC ; 3.2 mm average particle size) or steam-flaked corn (SFC ; 0.360 kg/L flake density)] was evaluated in conjunction with 4 levels of NDF from sugarcane bagasse (SCB ) as roughage source (RNDF ; 4%, 7%, 10%, and 13%; DM basis) to determine impact on growth performance, carcass characteristics, starch utilization, feeding behavior, and rumen morphometrics of Bos indicus beef cattle. Two hundred and forty Nellore bulls were blocked by initial BW (350 ± 37 kg), assigned to 32 feedlot pens and pens within weight block were randomly assigned, in a 2 × 4 factorial arrangement (2 corn processing and 4 levels of RNDF) to treatments. Effects of corn grain processing × RNDF level were not detected ( P ≥ 0.14) for growth performance, dietary net energy concentration, carcass traits, rumen morphometrics, and feeding behavior, except for time spent ruminating and time spent resting ( P ≤ 0.04), and a tendency for papillae width ( P ≤ 0.09). Bulls fed SFC-based diets consumed 7% less ( P = 0.001), had 10.6% greater carcass-adjusted ADG ( P < 0.001) and 19% greater carcass-adjusted feed efficiency ( P < 0.001) compared with bulls fed CGC-based diets. Observed net energy for maintenance and gain values were 14.9% and 19.4% greater ( P < 0.001), respectively, for SFC than for CGC-based diets. Fecal starch concentration was less ( P < 0.001) for bulls fed SFC compared with those fed CGC. No grain processing effects were detected ( P = 0.51) for rumenitis score; however, cattle fed SFC presented smaller ruminal absorptive surface area ( P = 0.03). Dry matter intake increased linearly ( P = 0.02) and carcass-adjusted feed efficiency tended ( P = 0.06) to decrease linearly as RNDF increased. Dietary RNDF concentration did not affect carcass characteristics ( P ≥ 0.19), except for dressing percentage, which tended to decrease linearly ( P = 0.06) as RNDF in finishing diets increased. Increasing RNDF in finishing diets had no effect ( P = 0.26) on time spent eating, but time spent ruminating and resting increased linearly (min/d; P < 0.001) with increased dietary RNDF. Steam flaking markedly increased flint corn energy value, net energy of diets, and animal growth performance, and led to improvements on feed efficiency when compared with grinding, regardless of RNDF content of diets. Increasing dietary RNDF compromised feedlot cattle feed efficiency and carcass dressing.